2003
DOI: 10.1007/s11837-003-0141-8
|View full text |Cite
|
Sign up to set email alerts
|

The compression stress-strain behavior of Sn-Ag-Cu solder

Abstract: The yield-stress behavior was investigated for the ternary lead-free solders using the compression stressstrain test technique. Cylindrical specimens were evaluated in the as-cast or aged (125°C, 24 h) condition. The tests were performed at -25°C, 25°C, 75°C, 125°C, and 160°C using strain rates of 4.2 × 10 -5 s -1 or 8.3 × 10 -4 s -1 . Specially designed Sn-Ag-0.6Cu samples were fabricated to compare the yield stress of the dendritic microstructure versus that of the equiaxed microstructure that occurs in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…As a further test, one would predict also that the ranking of the percentage of samples that experienced interface debonding should directly depend on the content of Cu in the solder alloy, the major strengthening influence in SAC solders. 29 Inspection of Table II shows that both of these predictions hold true for all of the observations made in this study after aging for 1,000 h if the Co-and Fe-containing solders are ignored. Of course, the accuracy of this analysis is undoubtedly Elevated Temperature Aging of Solder Joints Based on Sn-Ag-Cu: Effects on Joint Microstructure and Shear Strength 1491 dependent on the statistical significance of the number of joints that were tested, but it is still an interesting observation.…”
Section: Discussionsupporting
confidence: 57%
“…As a further test, one would predict also that the ranking of the percentage of samples that experienced interface debonding should directly depend on the content of Cu in the solder alloy, the major strengthening influence in SAC solders. 29 Inspection of Table II shows that both of these predictions hold true for all of the observations made in this study after aging for 1,000 h if the Co-and Fe-containing solders are ignored. Of course, the accuracy of this analysis is undoubtedly Elevated Temperature Aging of Solder Joints Based on Sn-Ag-Cu: Effects on Joint Microstructure and Shear Strength 1491 dependent on the statistical significance of the number of joints that were tested, but it is still an interesting observation.…”
Section: Discussionsupporting
confidence: 57%
“…For example, recent studies have shown that small differences in Cu content affect yield stress. 16 Therefore, it is important to establish an accurate and thorough database of time-dependent deformation for the Sn-Ag-0.6Cu composition, particularly for the development of a high-fidelity computational model that predicts the long-term reliability of soldered interconnections.…”
Section: Introductionmentioning
confidence: 99%
“…The compression test methodology was selected, based upon its successful use for measuring the time-independent properties of the Sn-Ag-0.6Cu solder. 2,16 The effect of the starting microstructure was examined through three test series. The first test series, the results of which are described in this report, used samples in the as-cast condition.…”
Section: Introductionmentioning
confidence: 99%
“…Because recent studies have shown that small differences in Cu content can affect the mechanical properties of Sn-Ag-Cu solders, it is important to determine the creep properties database specific to the Sn-Ag-0.6Cu composition in order to maximize the fidelity of the computational model predictions. 17 A study was undertaken to assess the creep properties of bulk Sn-Ag-0.6Cu solder. In the first part of the study, the creep behavior of the Sn-Ag-0.6Cu alloy was determined for specimens in the as-cast condition.…”
Section: Introductionmentioning
confidence: 99%